2017
DOI: 10.1016/j.nmni.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

First report of invasive liver abscess syndrome with endophthalmitis caused by a K2 serotype ST2398 hypervirulent Klebsiella pneumoniae in Germany, 2016

Abstract: We report a case of severe infection with liver abscess and endophthalmitis caused by a hypervirulent Klebsiella pneumoniae strain in an immunocompetent German male patient without travel history to Asia. Phenotypic and molecular characterization showed high similarity to the reference genome NTUH-K2044 isolated in Asia. The isolate was assigned as ST2398 (clonal complex 66). The findings underline global spread of hypervirulent Klebsiella pneumoniae strains to Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…Similarly, in this study we found 17 isolates that belonged to serotype K2 and the remaining 3 were nontypable. Serotype K2 has been identified in many countries, including China, Germany, Spain and Singapore [10, 19, 24, 27, 28]. Serotype K2 generally belongs to a diverse sequence of types, such as ST25, ST65, ST66 and ST86 [18].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in this study we found 17 isolates that belonged to serotype K2 and the remaining 3 were nontypable. Serotype K2 has been identified in many countries, including China, Germany, Spain and Singapore [10, 19, 24, 27, 28]. Serotype K2 generally belongs to a diverse sequence of types, such as ST25, ST65, ST66 and ST86 [18].…”
Section: Discussionmentioning
confidence: 99%
“…In order to test for a putative hypervirulence or hypermucoviscous phenotype, we established the so-called ‘string test’ [ 21 ]. The hypervirulent K. pneumoniae isolate of ST2398 possessing a K2 capsule was used as a positive control [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Raw reads were trimmed and assembled to contigs using SPAdes version 3.11.1 [26]. Acquired carbapenem resistance genes and multilocus STs were determined using ResFinder 2.1 [27] and Kleborate [28], respectively. CRKP isolates recovered from 2008 to 2013 in Zhejiang Province were unavailable.…”
Section: Carbapenemase-encoding Genes and Sequence Type Analysismentioning
confidence: 99%